Reorganization of Acyl Flux through the Lipid Metabolic Network in Oil-Accumulating Tobacco Leaves . Issue 2 (2nd December 2019) - Zhou, Xue-Rong; Bhandari, Sajina; Johnson, Brandon S.; Kotapati, Hari Kiran; Allen, Doug K.; Vanhercke, Thomas; Bates, Philip D.
Abstract : Engineering leaves to accumulate oils induced unexpected changes to fatty acid flux through the leaf lipid metabolic network. Abstract: The triacylglycerols (TAGs; i.e. oils) that accumulate in plants represent the most energy-dense form of biological carbon storage, and are used for food, fuels, and chemicals. The increasing human population and decreasing amount of arable land have amplified the need to produce plant oil more efficiently. Engineering plants to accumulate oils in vegetative tissues is a novel strategy, because most plants only accumulate large amounts of lipids in the seeds. Recently, tobacco ( Nicotiana tabacum ) leaves were engineered to accumulate oil at 15% of dry weight due to a push (increased fatty acid synthesis)-and-pull (increased final step of TAG biosynthesis) engineering strategy. However, to accumulate both TAG and essential membrane lipids, fatty acid flux through nonengineered reactions of the endogenous metabolic network must also adapt, which is not evident from total oil analysis. To increase our understanding of endogenous leaf lipid metabolism and its ability to adapt to metabolic engineering, we utilized a series of in vitro and in vivo experiments to characterize the path of acyl flux in wild-type and transgenic oil-accumulating tobacco leaves. Acyl flux around the phosphatidylcholine acyl editing cycle was the largest acyl flux reaction in wild-type and engineered tobacco leaves. In oil-accumulating leaves, acyl flux into the eukaryotic pathway of glycerolipid assembly was enhanced at the expense of the prokaryotic pathway. However, a direct Kennedy pathway of TAG biosynthesis was not detected, as acyl flux through phosphatidylcholine preceded the incorporation into TAG. These results provide insight into the plasticity and control of acyl lipid metabolism in leaves.